Promoting appreciation of cultural diversity and inclusion with the Stephanie Alexander Kitchen Garden Program. Issue 1 (13th April 2015) - Block, Karen; Gibbs, Lisa; Macfarlane, Susie; Townsend, Mardie
Abstract : Purpose: – The purpose of this paper is to present emergent findings from an evaluation of the Stephanie Alexander Kitchen Garden (SAKG) Program showing that the program promoted appreciation of cultural diversity and inclusion of culturally diverse groups. Design/methodology/approach: – The findings reported here are from the qualitative component of a mixed-method, nonrandomized, pre- and post-comparison evaluation study. Focus groups and interviews were held with school principals, teachers, program specialist staff, parents, volunteers and children at the program schools. Findings: – In a culturally diverse school, the program enhanced the school's capacity to engage and include children and families from migrant backgrounds. In less diverse settings, the program provided opportunities for schools to teach children about cultural diversity. Research limitations/implications: – Assessing the program's impact on multicultural education was not a specific objective of this study, rather these findings emerged as an unanticipated outcome during interviews and focus groups that explored participants' views on important changes to schools associated with the program. Thus, the quantitative component of the evaluation did not assess the extent of this program impact and further research is recommended. Practical implications: – The program may have particular value in culturally diverse schools, providing benefits in terms of engagement of children and families and potentially, in the longer term, associated improvements in learning outcomes. Social implications: – These findings suggest that the program can help to promote social equity and inclusion for culturally diverse groups. Originality/value: – This paper highlights critical equity implications associated with school-based programs' capacity to include culturally and linguistically diverse groups.